1998
DOI: 10.14430/arctic1050
|View full text |Cite
|
Sign up to set email alerts
|

Caribou Distribution During the Post-calving Period in Relation to Infrastructure in the Prudhoe Bay Oil Field, Alaska

Abstract: There is concern that caribou (Rangifer tarandus) may avoid roads and facilities (i.e., infrastructure) in the Prudhoe Bay oil field (PBOF) in northern Alaska, and that this avoidance can have negative effects on the animals. We quantified the relationship between caribou distribution and PBOF infrastructure during the post-calving period (mid-June to mid-August) with aerial surveys from 1990 to 1995. We conducted four to eight surveys per year with complete coverage of the PBOF. We identified active oil field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…First, we compared the observed and expected numbers of reindeer east and west of the peninsulas for each year using a test comparing expected density based on area available (Neu et al 1974, Cronin 1998) for testing our first prediction of reduced number of animals on the western side of the infrastructure. The size of the area east and west of the barrier was used to calculate the expected number relative to the observed numbers, removing areas covered with water.…”
Section: Discussionmentioning
confidence: 99%
“…First, we compared the observed and expected numbers of reindeer east and west of the peninsulas for each year using a test comparing expected density based on area available (Neu et al 1974, Cronin 1998) for testing our first prediction of reduced number of animals on the western side of the infrastructure. The size of the area east and west of the barrier was used to calculate the expected number relative to the observed numbers, removing areas covered with water.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is useful for quantifying specific thresholds in animal behavioral responses to habitat conditions, which can be difficult to identify directly from generalized linear models (Ficetola and Denoël , Boulanger et al ), even when disturbance covariates are incorporated (e.g., including a term for distance to disturbance in a GLMM). This approach also yielded results that could be evaluated in the context of earlier investigations of CAH densities within different 1‐km distance intervals to development (Cameron et al , ; Cronin et al ; Noel et al ).…”
Section: Methodsmentioning
confidence: 98%
“…The post-calving movements of cows with calves and accompanying individuals from the nearby calving grounds most likely account for the large caribou groups sighted in stratum 3. Cronin et al (1998) found that caribou were abundant in the Prudhoe Bay oil field and did not avoid oil field infrastructure. Bergerud et al (1984) provide several examples of caribou resilience to high levels of human disturbance.…”
Section: Two-way Analysis Of Variancementioning
confidence: 99%